Analysis of fibroblast pen usage amongst TikTok social media users. (17th May 2022) - Hernandez, Loren E.; Frech, Fabio; Mohsin, Noreen; Dreyfuss, Isabella; Nouri, Keyvan
Abstract: Social media networks serve as convenient platforms for the dissemination of information, including that which pertains to healthcare. However, social media networks may also disseminate incorrect information, and may even propagate potentially harmful skincare trends. Since its inception in 2016, TikTok, a social media platform wherein users can create and share videos, has served as a tool for the propagation of multiple, potentially dangerous cosmetic trends, most recently the usage of fibroblast pens. Fibroblast pens, also known as plasma pens, are toted to produce a variety of skincare benefits. However, many of the pens being sold commercially, and subsequently used on TikTok, are not FDA‐regulated. Potential adverse effects include the development of dyspigmentation, scarring, and mechanical burns of the skin. This study assessed social media content to improve our understanding of fibroblast pen usage amongst TikTok creators. An initial search of public TikTok posts tagged with "#PlasmaPen, " "#PlasmaPenTreatment, " "#FibroblastPlasma, " or "#FibroblastPlasmaPen" identified 200 posts, of which 78 were eliminated after accounting for overlapping posts between hashtags, posts that were later deleted by the user, and those in languages other than English. We analyzed posts according to creator type and classified them into four main themes. The 78 videos were later re‐viewed to provide more detailed subdivisions within the four main themes. Analysis showed that 36% of the posts were created by lay‐person TikTok users, followed by 25% of posts being created by self‐proclaimed fibroblast skin tightening specialists. Major themes include advertisement of the fibroblast pen (61%), experience with the fibroblast pen (26%), education on the fibroblast pen's uses and benefits (6.5%), and warnings related to usage of the pen (6.5%). TikTok users are more likely to encounter a post regarding fibroblast pen usage from uncredentialled, non‐medical professional accounts. Only 6.5% of posts were created with the intention of serving as a warning to users, with most of these posts being created by medical doctors. Dermatologists should be aware of the misinformation regarding fibroblast pens and consider posting on social media to raise awareness about this potentially dangerous skincare trend.